Altitude Acclimatization Alleviates the Hypoxia-Induced Suppression of Exogenous Glucose Oxidation During Steady-State Aerobic Exercise - Young, Andrew J.; Berryman, Claire E.; Kenefick, Robert W.; Derosier, Allyson N.; Margolis, Lee M.; Wilson, Marques A.; Carrigan, Christopher T.; Murphy, Nancy E.; Carbone, John W.; Rood, Jennifer C.; Pasiakos, Stefan M. (Frontiers in Physiology, 2018)
This study investigated how high-altitude (HA, 4300 m) acclimatization affected exogenous glucose oxidation during aerobic exercise. Sea-level (SL) residents (n=14 men) performed 80-min, metabolically-matched exercise (V̇O2 1.7 L/min) at SL and at HA < 5 h after arrival (acute HA, AHA) and following 22-d of HA acclimatization (chronic HA, CHA). During HA acclimatization, participants sustained a controlled negative energy balance (-40%) to simulate the “real world” conditions that lowlanders typically experience during HA sojourns. During exercise, participants consumed carbohydrate (CHO, n=8, 65.25 g fructose + 79.75 g glucose, 1.8 g carbohydrate/min) or placebo (PLA, n = 6). Total carbohydrate oxidation was determined by indirect calorimetry and exogenous glucose oxidation by tracer technique with 13C. Participants lost (P ≤ 0.05, mean ± sd) 7.9 ± 1.9 kg body mass during the HA acclimatization and energy deficit period. In CHO, total exogenous glucose (g) oxidized during the final 40 min of exercise was lower (P < 0.01) at AHA (7.4 ± 3.7 g) than SL (15.3 ± 2.2 g/min) and CHA (12.4 ± 2.3 g/min), but there were no differences between SL and CHA. Blood glucose and insulin increased (P ≤ 0.05) during the first 20 min of exercise in CHO, but not PLA. In CHO, glucose declined to pre-exercise concentrations as exercise continued at SL, but remained elevated (P ≤ 0.05) throughout exercise at AHA and CHA. Insulin increased during exercise in CHO, but the increase was greater (P ≤ 0.05) at AHA than at SL and CHA, which did not differ. Thus, while acute hypoxia suppressed exogenous glucose oxidation during endurance exercise, that hypoxic suppression is alleviated following altitude acclimatization and concomitant negative energy balance.